Clima social familiar y nivel de autoestima en adolescentes embarazadas, Hospital Tomas Lafora Guadalupe, 2015 - Ñiquen Villoslada, Carla Teresa (2015)
This study descriptive correlational research was conducted with the objective of determining the relationship between family social climate and level of self-esteem in pregnant adolescents seen at the Hospital of Guadalupe Thomas Lafora, 2015. The sample universe consisted of 49 adolescents pregnant. The instruments used for data collection were: Coopersmith Self-Esteem Inventory (Form Adult) Family and Social Climate Scale Moos, B.; Moos, R. and Trickett, E. The results are presented in statistical tables and charts to measure the relationship between variables the chi-square test was used. After conducted analysis was made the following findings: The self-esteem of pregnant adolescents is mostly middle and upper with 49 percent in both cases and family social climate also occurs more frequently in the average level (55.1 percent) followed by the familiar social climate high (32.7 percent). It was found that there is a statistically significant relationship between the two variables. Keywords: Family Social Climate, esteem, Adolescent Pregnancy.